PENGARUH KUALITAS PELAYANAN, CITRA MEREK, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN NILAI YANG DIPERSEPSIKAN SEBAGAI MEDIASI (Studi pada Konsumen Lazada.co.id Kota Semarang) - Jundi, Muhammad Said; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
The technological advances of the modern era led to the increasing penetration of internet users in the world, including Indonesia. This raises increased competition in the business world. This trend caused the emergence of the internet online stores. It is becoming the alternative choice in shopping for consumers. Consumers are not only able to shop in an offline store that requires out of the house, but now with the internet connection consumers can shop from home. It encourages the offline store to follow developments and make its own online store. But in fact the Indonesian people are still hesitant to purchase online. This phenomenon is evidenced by the data that showing of the 20 people there is only one person who bought at the online store, it is lower than offline stores where 5 people are at least 1 people are buying. For the online stores need to know how to increasing consumer purchasing decisions.The purpose of this study was to see how much influence service quality and brand image on perceived value and purchasing decision, and the influence of perceived value and trust towards purchasing decision This study is conducted to consumers who make purchases online at lazada.co.id, where respondents are Semarang people. The samples in this study were 200 respondents. The method of collecting data through questionnaires. The method of data collected through questionnaires. The sampling method in this study is a non-probability sampling with purposive sampling technique. This study uses analytical techniques of Structural Equation Model (SEM), which is estimated by AMOS 21.0.The Result show that the service quality and brand image has a positive and significant effect on perceived value. Service quality, brand image, trust and perceived value has a positive and significant effect on purchasing decision.